Tes Kepribadian Online Membentuk Kepribadianku, Benarkah?: Barnum Effect Ditinjau Dari Perbedaan Jenis Kelamin - Andi Widjannah Afdhal; Lukman; Ahmad Ridfah (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
Online personality tests are commonly used by adolescents who are in the process of self-discovery. This leads to a tendency for teenagers to self-diagnose based on their personality feedback. This study aims to investigate whether female adolescents are more prone to experiencing the Barnum effect and self-diagnosis compared to male adolescents. The study used purposive sampling to select participants, consisting of 300 students from SMAN 16 Makassar, with an equal distribution of 150 female and 150 male students aged 15-18 years. The Barnum Statement was employed as the measurement tool. Data analysis was conducted using the Chi-Square test, processed with SPSS version 26 for Windows. The results indicate that there is no significant difference between genders in terms of the barnum effect, with a significance value of p = 0.339. This study provides insights into the differences in the barnum effect between adolescent girls and boys.